Productivity model and analysis of influencing factors on horizontal fracture productivity in ultra-low permeability reservoir - Xiaofeng Wang; Binchi Hou; Hailong Dang; Houjun Tang; Pengxing Cui; Tao Gao (PLoS ONE, 2025)
Ultra-low permeability reservoir is characterized by the complex seepage law, Darcy’s law is not applicable to which and it is difficult to predict vertical well horizontal fracture productivity effectively. In this study, according to the law of equivalent percolation resistance, vertical well fracturing horizontal fracture seepage field is divided into two areas by pseudo-well assumptions: the reservoir external seepage resistance generated outside pseudo-well, where seepage flow is radial flow. Reservoir inner seepage resistance generated in pseudo-well, where seepage flow is vertical linear unidirectional flow. Based on principle of hydroelectricity similarity, the inner with the external seepage resistance were combined in series, the vertical well horizontal fracture productivity prediction model was established, and the productivity influence factors were analyzed by simulation. The results demonstrated that horizontal permeability had a great influence on oil production, and vertical permeability had little influence on the production. The bigger starting pressure gradient existed the critical value, the oil wells production showed a marked decline with the value bigger.